Free will, karma, and the cycle of death and rebirth: Rethinking determinism in Buddhist eschatology - Jessica Jessica (Life and Death: Journal of Eschatology, 2026)
Background: The debate over determinism and free will has traditionally centered on whether divine causation is compatible with human freedom, framed through compatibilist and incompatibilist positions in Western philosophy. Buddhist philosophy reframes this problem entirely: rather than divine will, it is karmic causality, the causal chain binding beings to samsara, the cycle of death and rebirth, that raises the question of whether freedom is possible at all. This shift from theistic to karmic determinism offers a distinct eschatological lens, since liberation (nirvana) in Buddhist thought is precisely the transcendence of causally-determined rebirth through the exercise of will, ethical action, and insight. Methods: This article analyzes Buddhist teachings on karma, dependent origination (pratītyasamutpāda), and liberation as a framework for resolving the determinism–free will debate, contrasted with Western theistic compatibilism and incompatibilism. Findings: Buddhist philosophy suggests karmic determinism and freedom are not strictly opposed: causal conditioning shapes but does not fully determine action, leaving space for volitional transformation (cetanā) that enables escape from the death-rebirth cycle. This reframes the classical debate around a soteriological rather than theological axis. Conclusion: Buddhist teachings offer a distinct eschatological resolution to the determinism–free will problem, locating freedom not in opposition to divine will but in the capacity to transcend karmic causality and the cycle of death and rebirth. Novelty/Originality of this article: This article shifts the determinism–free will debate from a theistic to a karmic-eschatological framework, addressing questions of mortality and liberation absent from Western treatments of the problem.